Chronic neuropathic pain: It’s about the rhythm - Alshelh, Z.; Harrington, Flavia; Youssef, A.M.; Reeves, J.M.; Macey, P.M.; Russell Vickers, E.; Peck, C.C.; Murray, G.M.; Henderson, L.A. (SOC NEUROSCIENCE, 2016)
© 2016 The Authors.